Tutoring the King: Juan Ginés de Sepúlveda's Victory over Bartolomé de las Casas. Issue 3 (March 2020) - SPEER, MARY
Abstract : This article claims that four primary sources written by Juan Ginés de Sepúlveda demonstrate a strong link of influence between Sepúlveda and Philip II: a letter from Sepúlveda written to Prince Philip only a year prior to the great debate between Sepúlveda and Bartolomé de las Casas in 1550; Sepulveda's dedication of his translation of Aristotle's Politics to Philip (1548 ); Democrates Secundus [Demócrates segundo] (1544), a dialogue arguing that war against the Amerindians is just; and Democrates Primus [Demócrates primero] (1535), a dialogue arguing against Erasmus's pacifism and for the enrichment of the Church. Sepúlveda's close relationship to Philip as his former childhood tutor, the linguistic and argumentative affinity between the four documents, and Philip's subsequent attitude and policy decisions suggest that Sepúlveda's thought in Democrates Secundus was aimed at the future king and influenced Philip's decision to continue the encomendero system in the Indies after Charles V abdicated in 1556 in spite of Las Casas's objections.